2021
DOI: 10.4236/jss.2021.92025
|View full text |Cite
|
Sign up to set email alerts
|

Examining Factors Contributing to Eritrea’s Successful COVID-19 Response

Abstract: The COVID-19 pandemic has been one of the greatest global crises in decades. To date, around the world tens of millions of cases have been confirmed, nearly two million people have died, and the livelihoods of billions have been greatly affected. While COVID-19 has been a truly global problem, infection and death rates in many African countries have been much lower than originally feared. One COVID-19 success story is Eritrea, a young, developing country in Northeast Africa that, by late December 2020, reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Thus, subduing the COVID-19 was given a high priority for many countries. In response, Eritrea applied stricter measures that attained a substantial outcome in the rate of infection and death cases 61,62 . In addition, lockdown measures and early implementation were related to positive results 63 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, subduing the COVID-19 was given a high priority for many countries. In response, Eritrea applied stricter measures that attained a substantial outcome in the rate of infection and death cases 61,62 . In addition, lockdown measures and early implementation were related to positive results 63 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lockdown measures and early implementation were related to positive results 63 . Other reasons for the reduced cases and deaths in the Horn of Africa, particularly in Eritrea, were the demographics, low volume of global air traffic, and a moderately young population that played a positive part in slowing down the pandemic 62 . In general, as many studies have reported diseases associated with severe illness and death from COVID-19, regularly connected with older populations, such as for overweight, hypertension, cardiovascular diseases, chronic lung infection, malignancy, and diabetes, are less predominant in the region 52 , 62 , 64 .…”
Section: Discussionmentioning
confidence: 99%
“…In late March 2020, the closing of all institutions of learning, restaurants, and cafés, the shutting down of all public and private transport as well as a prohibition on intercity travel, followed the implementation of the National Preparedness and Response Plan designed in collaboration with the WHO and other international organisations. A total nationwide lockdown was declared in early April 2020 and then extended, becoming one of the most stringent in the world (Amahazion 2021). Although the consequences of this lockdown are still unexplored, it is logical to assume that the lockdown must have had adverse eff ects on income-generation activities such as petty trade, but also agricultural and pastoral activities, thus increasing dependency on private remittances.…”
Section: Guesstimating Financial Remittances: Amount and Featuresmentioning
confidence: 99%